Insomnia: psychological and neurobiological aspects and non-pharmacological treatments - Yara Fleury Molen; Luciane Bizari Coin Carvalho; Lucila Bizari Fernandes do Prado; Gilmar Fernandes do Prado (Arquivos de Neuro-Psiquiatria)
Insomnia involves difficulty in falling asleep, maintaining sleep or having refreshing sleep. This review gathers the existing informations seeking to explain insomnia, including those that focus on psychological aspects and those considered neurobiological. Insomnia has been defined in psychological (cognitive components, such as worries and rumination, and behavioral aspects, such as classic conditioning) and physiological terms (increased metabolic rate, with increased muscle tone, heart rate and temperature). From the neurobiological point of view, there are two perspectives: one which proposes that insomnia occurs in association with a failure to inhibit wakefulness and another that considers hyperarousal as having an important role in the physiology of sleep. The non-pharmacological interventions developed to face different aspects of insomnia are presented.